Landslides on the late Quaternary deposits in the Bhote Koshi area, central Nepal - Higaki, D.; Yagi, H.; Asahi, K.; Miyake, N. (Journal of Nepal Geological Society, 2000)
ABSTRACT The origin and age of piedmont talus slopes and their relationship with present landslides are studied in the Bhote Koshi area of central Nepal. The talus slopes near Lamosanghu consist of 7-15 m thick boulder-rich colluvium overlying the Middle terrace deposits of the Sun Koshi River. The organic debris within these layers was dated 12,745±160 years BP (Nu-967) and 12,970±100 years BP (Beta-130478).The pollen analysis of the sediments revealed that a cool temperate to subalpine conifer forests existed in the adjacent area, and marshland was formed near the Sun Koshi River. According to the limited distribution of glacial landforms above 4.000 m in the upper Bhote Koshi watershed, the upper talus slope deposits had not originated from glaciation, but from frequent landslides on the higher slopes 12,000- 13,000 years ago, presumably during the latest Last Glacial time and the early Holocene. The talus deposits were formed by block sliding on the alternating bands of phyllite and quartzite. On the other hand, near the Main Central Thrust, abundant groundwater is available to trigger present frequent landslides on the talus slopes.